THE SOP ANALYSIS AND DESIGN OF INCOME REPORTING SYSTEM FROM ARTICLE 21 AND 23 - Haki, Elisabeth Yuliana; Handoko, Jesica (Research In Management and Accounting (RIMA), 2022)
The object of research is PT PMTextile which is engaged in the textile industry. The company's SOP is irrelevant to the company's current practices and is not yet in accordance with tax regulations. This research aims to analyze and redesign the SOP of the income tax reporting system article 23 and 21. The problems are there is no SOP correction of periodic income tax return, there is no authorization, the documents are still less relevant, references to SOP regulations and policies are not appropriate. Lastly, there is no independent checking, the signing of tax returns and SOP of income tax reporting article 23 has not used e-bupot. This research aims to analyze and redesign the SOP to improve internal control. This research uses a type of qualitative descriptive research. The result is to adjust the company's SOP to the company's condition and redesign it, add checking and authorization activities, changes in document flow, adjustment of references to regulations and policies SOP in accordance with tax regulations, and the proposed SOP correction of periodic income tax return article 23 and 21. PT PMTextile is expected to conducts a routine evaluation of its SOP and update tax regulations.